88.0k views
4 votes
I have 3 questions. Please number the answers.

#1: What is the expression (3x - 5) + (-4x + 1) simplified?
#2: What is the expression 6(-2.1k - 2) + (7k +5) simplified?
#3: What is the expression (2m + 7) - (3 - 4m) simplified?

User River Tam
by
4.6k points

1 Answer

2 votes
1.
(3x - 5 ) + (-4x + 1)
= 3x - 4x -5 + 1
= -x - 4

2.
6(-2.1k - 2) + (7k + 5)
= (-12.6k - 12) + (7k + 5)
= -12.6k + 7k - 12 + 5
= -5.6k - 7

3.
(2m + 7) - (3 - 4m)
= 2m + 7 - 3 + 4m
= 6m + 4
User Timdisney
by
5.0k points